AUGMENTED REALITY BASED IMAGE TRACKING FOR INTRODUCE PUPPET SHADOW TRADITIONAL MUSICAL INSTRUMENT - Krisna Subarkah; Muhamad Azrino Gustalika; Pradana Ananda Raharja (Jurnal Teknik Informatika (Jutif), 2023)
With the development of science and technology, traditional musical instruments are starting to be abandoned, one of the factors is the ease of playing modern musical instruments, and traditional musical instruments are also rarely found in everyday life. With the progress of today's era, AR (Augmented Reality) technology was born. The way Augmented Reality works is by scanning a sign or marker. This research aims to build an application with augmented reality technology to introduce traditional shadow puppets musical instruments. This research was designed using the MDLC (Multimedia Development Life Cycle) method. They were testing the application using blackbox testing on two smartphones with different specifications, with the result that both smartphones could run the application properly. Then for testing the use of the application using the heuristic evaluation method carried out by an expert with the highest severity rating value on the visibility of system status with a value of 0.625. The result of this research is the application of traditional shadow puppets musical instruments based on augmented reality, which is expected to be used to introduce traditional shadow puppets musical instruments.